2017
DOI: 10.1177/0956797617702014
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Associations Between One’s Partner and One’s Affect as the Proximal Mechanism of Change in Relationship Satisfaction: Evidence From Evaluative Conditioning

Abstract: The current study examined whether directly altering affective associations involving a relationship partner through evaluative conditioning can lead to changes in relationship satisfaction. Married couples ( N = 144) were asked to view a brief stream of images once every 3 days for 6 weeks. Embedded in this stream were pictures of the partner, which, according to random assignment of couples to experimental group, were paired with either positive or neutral stimuli. Couples also completed measures of automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(97 citation statements)
references
References 46 publications
4
93
0
Order By: Relevance
“…To our knowledge, however, nothing is known about the effect of the actor’s implicit partner evaluations on the partner’s outcomes. One reason why may be that individuals’ own implicit self-evaluations ( McNulty, Baker, & Olson, 2014 ) and own emotional experiences that become associated with their partner ( Hicks et al, 2016 ; McNulty, Olson, Jones, & Acosta, 2017 ) shape their own implicit partner evaluations, which therefore strongly influence their own outcomes over time ( McNulty & Olson, 2015 ) but not necessarily those of their partner, which are more likely to be determined by their own implicit evaluations. Yet, following the idea that more positive implicit partner evaluations promote constructive nonverbal behaviors in dyadic interactions, one may expect that partners could also be positively affected by these behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, however, nothing is known about the effect of the actor’s implicit partner evaluations on the partner’s outcomes. One reason why may be that individuals’ own implicit self-evaluations ( McNulty, Baker, & Olson, 2014 ) and own emotional experiences that become associated with their partner ( Hicks et al, 2016 ; McNulty, Olson, Jones, & Acosta, 2017 ) shape their own implicit partner evaluations, which therefore strongly influence their own outcomes over time ( McNulty & Olson, 2015 ) but not necessarily those of their partner, which are more likely to be determined by their own implicit evaluations. Yet, following the idea that more positive implicit partner evaluations promote constructive nonverbal behaviors in dyadic interactions, one may expect that partners could also be positively affected by these behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the pairings' base‐rate may moderate learning, with slightly variable base‐rates (e.g., 75% Squarefaces = bad/Longfaces = good) resulting in greater learning (Brauer, Er‐rafiy, Kawakami, & Phills, ). Finally, learning may be facilitated when pairings are repeated across multiple occasions, shown to more effectively alter implicit evaluations in both adults (McNulty, Olson, Jones, & Acosta, ) and children (Qian et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies targeted automatic processes toward anxiety [ 21 , 39 ], and one study targeted automatic processing toward both anxiety and depression [ 20 ]. In addition, one study was found for insomnia [ 34 ], self-injurious thoughts and behaviors [ 41 ], attitudes toward homosexuality and self-esteem in gay men [ 42 ], and relationship satisfaction in marriages [ 43 ]. Follow-up periods also varied and ranged from no follow-up (n=4 studies [ 39 , 42 , 44 , 45 ]) to the longest follow-up period of 6 months [ 35 ].…”
Section: Resultsmentioning
confidence: 99%